Interactional competencies in medical student admission: what makes a “good medical doctor”? - Fleck, Leonie; Amelung, Dorothee; Fuchs, Anna; Mayer, Benjamin Emeran; Escher, Malvin; Listunova, Lena; Schultz, Jobst-Hendrik; Möltner, Andreas; Schütte, Clara; Wittenberg, Tim; Schneider, Isabella; Herpertz, Sabine (Advances in health sciences education, 2025)
Doctors’ interactional competencies play a crucial role in patient satisfaction, well-being, and compliance. Accordingly, it is in medical schools’ interest to select candidates with strong interactional abilities. While Multiple Mini Interviews (MMIs) provide a useful context to assess such abilities, the evaluation of candidate performance during MMIs is not always based on a solid theoretical framework. The newly developed selection procedure “Interactional Competencies - Medical Doctors (IC-MD)” uses an MMI circuit with five simulation patient scenarios and is rated based on the theoretically and empirically grounded construct of emotional availability. A first validation study with N = 70 first-semester medical students took place in 2021. In terms of convergent validity, IC-MD ratings showed strong correlations with simulation patients’ satisfaction with the encounter (r =.57) but no association with emotional intelligence measures. IC-MD ratings were not related to high school performance or a cognitive student aptitude test, indicating divergent validity. Inter-rater reliability (ICC = 0.63) and generalizability (Eρ2 = 0.64) were satisfactory. The IC-MD proved to be fair regarding participants’ age and gender. Participants with prior work experience in healthcare outperformed those without such experience. Participant acceptance of the procedure were good. The IC-MD is a promising selection procedure capable of assessing interactional competencies relevant to the medical setting. Measures of interactional competencies can complement the use of cognitive selection criteria in medical student admission. The predictive validity of the IC-MD needs to be addressed in future studies.
Online veröffentlicht: 15. Juli 2024
Gesehen am 16.12.2024